2011
DOI: 10.5897/ajb11.329
|View full text |Cite
|
Sign up to set email alerts
|

Seed viability, germination and seedling growth of canola (Brassica napus L.) as influenced by chemical mutagens

Abstract: Mutation induction is considered as an effective way to enrich plant genetic variation, particularly for traits with a very low level of genetic variation. The objectives of this study were to evaluate the effect of different dosages of chemical mutagens on seed germination, seed viability and seedling growth characteristics and to identify optimum treatment conditions for chemical mutagens based on the LD 50 criterion in canola (Brassica napus L.). Two pretreatment conditions of soaking in distilled water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The works of Emrani et al, 2011;Anbarasan et al, 2013;Anbarasan et al, 2015, Kumari et al, 2016 sesame genotypes observed a dose dependent reduction in germination percentage. Gamma rays interfere with metabolic process of the mutated seeds causing physiological changes coupled with chromosomal damage leads to inhibitory effect on seed germination (SJODIN, 1962 andSinha andGodward,1972).…”
Section: Resultsmentioning
confidence: 95%
“…The works of Emrani et al, 2011;Anbarasan et al, 2013;Anbarasan et al, 2015, Kumari et al, 2016 sesame genotypes observed a dose dependent reduction in germination percentage. Gamma rays interfere with metabolic process of the mutated seeds causing physiological changes coupled with chromosomal damage leads to inhibitory effect on seed germination (SJODIN, 1962 andSinha andGodward,1972).…”
Section: Resultsmentioning
confidence: 95%